2001
DOI: 10.1016/s0014-5793(01)03220-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel progestogen receptor subtype in the Japanese eel, Anguilla japonica1

Abstract: A cDNA encoding a second type of a progestogen receptor (ePR2) was isolated from the same library as we had previously cloned a functional PR (ePR1) in eel testis. The amino acid sequence of the ePR2 shows low homology with ePR1 (34%), but both PRs showed progestogen-dependent transactivation in transfection experiment. Tissue distribution of ePR2 mRNA was clearly different from that of ePR1. Protein interaction between two PRs was demonstrated in vitro by a glutathione S-transferase pull-down assay. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 35 publications
4
46
0
Order By: Relevance
“…After DNase I treatment, 5 g of RNA was transcribed by Superscript II (Invitrogen) by using an oligo (dT) primer. The resulting cDNA was amplified by PCR with ePR I-specific primers (sense primer, 5Ј-CAACTTGGATATGGCGAACAGC-3Ј; antisense primer, 5Ј-TGGCACCAAAACGGAGAATCCG-3Ј) and ePR II-specific primers (sense primer, 5Ј-CGACTTCGAACAGCTCGTA-TGG-3Ј; antisense primer, 5Ј-CTTTGAGATTCTGGAGAC-GAG-3Ј), which were designed based on published eel PR I and II sequences (36,37). The PCR cycling parameters were as follows: 25 cycles of 94°C for 30 sec, 58°C for 30 sec, and 72°C for 30 sec.…”
Section: Measurement Of 20␤-hydroxysteroid Dehydrogenase Activity In mentioning
confidence: 99%
“…After DNase I treatment, 5 g of RNA was transcribed by Superscript II (Invitrogen) by using an oligo (dT) primer. The resulting cDNA was amplified by PCR with ePR I-specific primers (sense primer, 5Ј-CAACTTGGATATGGCGAACAGC-3Ј; antisense primer, 5Ј-TGGCACCAAAACGGAGAATCCG-3Ј) and ePR II-specific primers (sense primer, 5Ј-CGACTTCGAACAGCTCGTA-TGG-3Ј; antisense primer, 5Ј-CTTTGAGATTCTGGAGAC-GAG-3Ј), which were designed based on published eel PR I and II sequences (36,37). The PCR cycling parameters were as follows: 25 cycles of 94°C for 30 sec, 58°C for 30 sec, and 72°C for 30 sec.…”
Section: Measurement Of 20␤-hydroxysteroid Dehydrogenase Activity In mentioning
confidence: 99%
“…In this study, we identified duplicated nuclear progestin receptor genes (pgr1 and pgr2) in the genomes of the European and Japanese eels, in agreement with the previous cloning of two progestin receptors from Japanese eel testis (ePR1 and ePR2 Todo et al, 2000;Ikeuchi et al, 2002). In contrast, a single PGR has been reported in pufferfish (Takifugu rubripes), tetraodon (Tetraodon nigroviridis), zebrafish, medaka (Oryzias latipes), and stickleback (Hanna et al, 2010).…”
Section: Duplicated Nuclear Progestin Receptors In the Eelsupporting
confidence: 90%
“…Both were mainly expressed in the pituitary and in the brain in female eel, while in males they were mainly expressed in the gonads and in other tissues outside the BPG axis (pgr1 in kidney and muscle, pgr2 in the gill). The tissue distribution of nPRs in the European eel is similar to what was found in the Japanese eel (Ikeuchi et al, 2002). Nevertheless, the different nPR tissue distribution found among teleosts may indicate species-specific differences of the nPR function.…”
Section: Differential Tissue Distribution Of Progestin Receptorssupporting
confidence: 74%
See 2 more Smart Citations